Do direito de visita íntima? - Celestino, Bruno de Omena (2025)
The purpose of this research is to define the basis and legal nature of conjugal visits for people deprived of their liberty due to criminal convictions, to understand and define how they are positioned in the Brazilian legal system. The problem that motivates the research can be defined by the following questions: are conjugal visits a right that can be exercised by human beings who are serving sentences, allowing those who are imprisoned to have the right to receive visits to have sexual relations with people outside the prison establishment? If it is a right, what is its basis? The initial hypothesis of the research is that a conjugal visit is a right that can be enforced against the State by the imprisoned person and can be analyzed through the purposes of the sentences and their constitutional grounds, or that it would oblige the State to provide suitable places for the practice of conjugal visits. The research method used is hypothetical-deductive, through a literature review. The results obtained by the research were divided into five chapters. The first chapter was devoted to the presentation of what is called the Problem of Sex in Prison, a term used for the first studies that focused on analyzing the consequences of the limitations imposed on sexual practices during deprivation of liberty. The second chapter discussed the main theories of intimate visits, focusing not only on their emergence, from an informal practice to the current form of practice regulated by the State. The third chapter discussed the normative bases of conjugal visits in the Brazilian legal system, whether at the constitutional, "suprale- gal", legal and regulatory levels, and included studies of how intimate visits are treated in other countries, when they exist. The fourth chapter explores the shortcomings of the main theories and hypotheses on the subjeet, focusing on criticism from a criminal law studies perspective. In the fifth and final chapter, based on the results presented in the previous chapters, and by carrying out a criminal law studies based on the specificities of the criminal sanction and its constitutional foundations, it was possible to confirm the hypothesis that conjugal visits would be a type of fundamental right arising from the constitutional principles of humanity and indi- vidualization of criminal sanction, having, furthermore, accidental basis, which would generate consequences in the constitutional interpretation of the laws that deal with intimate visits. At the end, the conclusions of the research were presented in a separate chapter, where the theses that were reached and the consequences derived from them were exposed